RISK AND OPPORTUNITY MANAGEMENT IN MEP PROJECT-BASED COMPANIES AND ITS IMPACT ON BUSINESS PERFORMANCE (American International Journal of Business and Management Studies, 2024)
The board is crucial for MEP project-based organizations to progress. Gamble the board prevents cost overruns and project delays, while opportunity the executives capitalize on excellent opportunities. Chance administration in Pakistan's growth is the study's main focus, and Chance mechanical, electrical, and plumbing (MEP) management in project board in Pakistani development is reviewed. The evaluation included several hundred development (MEP) projects from Karachi, Lahore, Faisalabad, Rawalpindi, Islamabad Pakistan's five largest cities with active development and large investments. Surveys are sent to company managers via group inspection, and 250 responses are received mechanical, electrical, and plumbing (MEP) projects management. Data is analyzed using Savvy PLS's structured condition presentation. Business performance is connected to the board systems that are based on proven evidence, evaluation, checking and helped the construction project succeed. Risk executives' methods fundamentally and well affected job completion, according to the assessment. Understanding executive risk valuation is much better. The results reveal that that in terms of genuine development projects, an efficiency study may present a fuller picture of risk the board in various enterprises. The practice of conducting systematic audits to assess the philosophy of writing is rarely employed in the execution of executive projects and risk analysis. The results revealed that the effective mechanical, electrical, and plumbing (MEP) performance of the board tactics is in improving project execution in Pakistan. The exploratory approach is employed to integrate previous studies on risk management executives and the implementation of business ventures in the field of development.JEL Classification Codes: G32.